FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN - Astrid Aurelia Prasetyo; Jamaludin Iskak (Jurnal Paradigma Akuntansi, 2023)
This research aims at how the effect of liquidity, firm size and financial condition on going concern audit opinion on manufacturing company listed on the Indonesia Stock Exchange during 2017-2019. Sample was selected using purposive sampling method and the valid data was 30 companies. Data processing techniques using logistic regression analysis what helped by SPSS program (Statistical Product and Service Solution) for Windows released 25 and Microsoft Excel 2013. The results of this study indicate that liquidity and financial condition have a significant influence on going concern audit opinion. The implication of this study is the need to planning considerations that can improve company's financial condition so that the company is free from going concern audit opinion by auditors.